2008
DOI: 10.1158/0008-5472.can-07-6100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of mPGES-1 Suppresses Intestinal Tumorigenesis

Abstract: Elevated levels of prostaglandin E 2 (PGE 2 ) are often found in colorectal cancers. Thus, nonsteroidal anti-inflammatory drugs, including selective cyclooxygenase-2 (COX-2) inhibitors, are among the most promising chemopreventive agents for colorectal cancer. However, their long-term use is restricted by the occurrence of adverse events believed to be associated with a global reduction in prostaglandin production. In the present study, we evaluated the chemopreventive efficacy of targeting the terminal syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
129
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 43 publications
14
129
1
Order By: Relevance
“…As demonstrated in a study by Nakanishi et al (2008), we have herein found that AOM-induced pre-neoplastic ACF formation in an early phase of colon carcinogenesis was suppressed by the lack of mPGES-1, with a reduction in the number of large ACF (Figure 4). In addition, we further found that the formation of large ACF was enhanced by transgenic overexpression of mPGES-1, although spontaneous colon carcinogenesis did not occur.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As demonstrated in a study by Nakanishi et al (2008), we have herein found that AOM-induced pre-neoplastic ACF formation in an early phase of colon carcinogenesis was suppressed by the lack of mPGES-1, with a reduction in the number of large ACF (Figure 4). In addition, we further found that the formation of large ACF was enhanced by transgenic overexpression of mPGES-1, although spontaneous colon carcinogenesis did not occur.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we found that mPGES-1 deficiency suppresses chemical carcinogen-induced colon Figure 1, genetic deletion of mPGES-1 significantly reduced both the total number and size of polyps in the colon after AOM administration. Nakanishi et al (2008) also recently reported that the introduction of mPGES-1 gene deletion onto Apc D14/ þ mice, in which spontaneous intestinal and colon carcinogenesis occurred, reduced the number and size of polyps. Taken together with this previous report, this study has provided additional lines of evidence that mPGES-1-derived PGE 2 promotes multiple steps in colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 87%
“…Consistently, disruption of the mPGES-1 gene also suppressed intestinal polyposis in other Apc gene mutant mice (Nakanishi et al 2008). Moreover, blocking PGE 2 signaling through the EP2 receptor led to significant suppression of polyp formation in Apc ∆716 mice (Sonoshita et al 2001).…”
Section: The Cox-2/pge 2 Pathway and Intestinal Tumorigenesismentioning
confidence: 68%
“…So inhibiting the expression of mPGES-1 may be a potential therapeutic target in clinical practice (Murakami et al, 2000). Nakanishi has demonstrated that genetic deletion of mPGES-1 could suppress intestinal and lung tumorigenesis in vivo animal trials (Nakanishi et al, 2008;Pecchi et al, 2008). Cheng et al (2006) has reported that mPGES-1 inhibitor could block PGE2 and make therapeutic effects in many diseases instead of nonsteroidal anti-inflammatory drugs (NSAIDs), meanwhile, no obvious side effects were observed.…”
Section: Discussionmentioning
confidence: 99%